Environmentally sustainable laundering practices of selected Filipino households - Baydo, Kimberly R. author (College of Home Economics, University of the Philippines Diliman, 2016)
The largest environmental impact from clothing comes from the washing process after it has been purchased. This contributes to 80% of the total carbon footprint of a garment (Claudio, 2007). With this, it is reasonable to start paying more attention to laundering. This study aimed to compare the laundering practices of selected households in UP Diliman with environmentally sustainable practices gathered from literature. A checklist of sustainable laundering practices was formulated based on different existing studies about laundering and sustainability. Through stratified convenience sampling, 30 households living inside the University of the Philippines Diliman campus were selected and interviewed about their laundering practices. These practices were compared to the checklist for environmentally sustainable laundering practices. The study found that, not all but, majority of these households practice environmentally sustainability in most laundering practices, specifically in frequency of laundering, sorting, pre-treating, soaping, using of water, and drying. The reasons behind the non- environmentally sustainable practices of households were the warm climate, cost or lack of greener choices, and the lack of knowledge and available information about sustainable laundering. On the other hand, the reasons behind the environmentally sustainable practices were more of the practical and economical factors rather than environmental. These households aimed to save and efficiently use materials like water and electricity to save on bills without realizing that they were actually saving the environment as well. The results suggest the need for information dissemination about environmental sustainability in laundering among Filipino households.